PENGARUH PEMBERIAN PEREGANGAN (STRETCHING) TERHADAP PENURUNAN KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA PERAJIN LOGAM KAMPUNG BASEN KOTAGEDE YOGYAKARTA TAHUN 2017 - Sri Yuni (Universitas Respati Yogyakarta, 2018)
The background of this research is the prevalence of musculoskeletal disease in Indonesia, based on diagnosis by health personnel is 11.9 percent and based on diagnosis or symptoms that is 24.7 percent. Ninety percent of Low Back Pain cases are not caused by organic abnormalities, but by body position mistakes in work. Sitting for a long time is the biggest cause of lower back pain. Stretching should be done to move the muscles in the lower back and for blood circulation smoothly. This method is useful for workers to avoid back problems. From the data recorded that 65 metal craftsmen in Kampung Basen, about 36 of them have moderate low back pain and 29 of them have mild back pain.The purpose of this research was to determine the effect of stretching on low back pain complaints of metal crafters in Kampung Basen Kotagede Yogyakarta.The method in this research is quantitative research with quasi experimental approach and using Non-Equivalent Control Group design. Sampling in this research using purposive sampling technique and data analysis used is univariate and bivariate analysis using man-whitney.Based on the results of analysis it is known that there is an effect of stretching on lowering of low back pain of metal crafters on Basen Village Kotagede Yogyakarta with p value 0,017 (<0,05) and Z value -2,392 ( > 1.96).Keyword : Stretching, Low Back Pain, Metal Craftmen